WWW.DISSERS.RU


...
    !

 >> 
N = 2 N = 1 N = 1 N = 2 N = 2 N = 2 N = 2 N = 1 N = 1 D N = 1 N = 2 CP (N -1) N = 2 N = 1 2S()/(x)(y) S() (x) S() 2() =, i i (x) i i 2 i 2() i 2() 1 i N = 1 SU(2) 10 V = 32, |v|6 v2 = Qk Qk Q Q k = 1, 2 N = 2 N = 2 SU(2) N = 2 4 dS d3uS 1 VIN =2 = - d4x d2 d2 d21 d22 42 S 22 (a2)2 42 2 exp - 2 aa - 2 i(Df SauSDf )a, g2 S 2g2 S a N = 2 a = 1, 2, 3 f D f = 1, 2 g2 x S uS 1 2 N = 2 SU(2) Nf N = 2 N = 2 N U(1)N-1 U(1) SU(2) N = 2 N = 2 N = 1 23 (QQ)2 1 Weff = i mQQ + - 4 QQ 1 N = 2 m 6 1 y2 = x3 - ux2 + m3x -, 1 16 2 u =< a /2 > a N = 1 N = 2 SU(2) U(1) U(1) Z2 2 Mm exp -, T Mm T 2v2 T =, log m L v m L L/ log L L N = 1 N = 2 N = 2 SU(N + 1) SU(N) U(1) N = 2 SU(N) (N)C+F (N)C+F (1 + 1) N = (2, 2) CP (N - 1) S(1+1) = 2 dt dz (k nk n) + (nk n)2, n t, z k = 0, 3 2 =. g2 N CP (N -1) SU(N) BP S CP (N - 1) CP (N - 1) (3 + 1) (1 + 1) N = 2 CP (N - 1) N = 2 N = 1 N = 1 N = 1 N = 2 N = 2 (N) (N) N = 2 (N) Nf = N N = 2 N = 1 N = (2, 2) (N - 1) N = (0, 2) (N - 1) (N - 1) N N = (0, 2) N N T = 2 + 2 1 - e-u, 4 CP (N -1) u N = 1 N = 1 (N - 1) N = 2 M N = 2 N = 1 N = 2 CP (N - 1) N 2 2k T = 2 + c1 N 2 1 + c2, N k = 0, 1,..., (N - 1) c1 c2 D BP S D D D D SU(N) N D BP S N = 1 N D D U(1) N = 2 SU(2) m1 m2 m1 m2 SU(2) U(1) BP S U(1) U(1) (2 + 1) U(1) N = 2 SU(3) r = 2 SU(3) SU(2)U(1) BP S r = 2 U(1) U(1) 1/4 BP S N = 2 U(N) Nf = N (1 + 1) N = 2 CP (N - 1) N (1 + 1) CP (N - 1) (3+ 1) N = 2 U(N) (1+1) N = (2, 2) CP (N - 1) N = 2 U(N) N = (0, 2) CP (N - 1) N U(N) CP (N -1) N D N = 2 U(1) 1/4 N = 2 N = 2 N = 2 SU(2) L/ log L L N = 1 N = 2 SU(2) N = 1 N = 2 N = 2 N = 1 N N = (0, 2) (N - 1) N = 1 N-1 CP N = 1
 >> 





2011 www.dissers.ru -

, .
, , , , 1-2 .